Potential antiinflammatory effects of acupuncture in a chronic stress model of depression in rats. (8th April 2016) - Lu, Jun; Shao, Run-Hui; Hu, Li; Tu, Ya; Guo, Jian-You
Highlights: Acupuncture treatment alleviates the depressive-like behavior in CUMS rats. Acupuncture treatment reduces the mRNA and protein expressions of IL-1β, IL-6 and TNF-α in the hippocampus and prefrontal cortex in CUMS rats. Acupuncture treatment decreases the levels of IL-1β, IL-6 and TNF-α in the serum of CUMS rats. Abstract: Accumulating evidence indicates that inflammation may contribute to the pathophysiology of depression. Acupuncture in traditional Chinese medicine has been considered an effective treatment for depression. However, whether the mechanisms that underlie the antidepressant effect of acupuncture are related to its antiinflammatory properties remains unclear. In the present study, rats were exposed to chronic unpredictable mild stress (CUMS) for 28 days to induce depressive-like behavior. Body weight, sucrose preference, and locomotor activity in the open field were measured. After the behavioral tests, reverse transcription polymerase chain reaction was used to determine the mRNA expression of proinflammatory cytokines (interleukin-1β [IL-1β], interleukin-6 [IL-6], and tumor necrosis factor-α [TNF-α]), and enzyme-linked immunosorbent assay was used to detect cytokine concentrations. CUMS rats exhibited decrease in body weight, sucrose preference, and locomotor activity in the open field test. Chronic acupuncture and fluoxetine treatment reversed CUMS-induced depressive-like behavior. Compared with control rats, the mRNA and protein expression of IL-1β, IL-6, and TNF-α in the hippocampus and prefrontal cortex and cytokine concentrations in serum significantly increased in CUMS rats. Acupuncture and fluoxetine treatment significantly decreased the levels of proinflammatory cytokines in the hippocampus, prefrontal cortex, and serum. These results suggest that acupuncture has antidepressant-like effects, and its mechanism of action appears to involve the inhibition of proinflammatory cytokines.